Impact of Future Wireless Networks in the Telecommunication Sector – A Review - Joby, P P (Journal of Electronics and Informatics, 2024)
A wireless network utilizes wireless data links between its nodes, eliminating the need for expensive cabling within buildings or between different equipment locations in households, telecommunications networks, and corporate installations. Different cellular networks exist, including 1G, 2G, 3G, 4G, and 5G. The transition to each new generation occurred due to specific drawbacks. Presently, 5G is considered the network of the future. This review will explain one of the most recently developed 5G networks, providing a detailed explanation of the evolution, effect, merits and demerits, and obstacles. Additionally, it provides an explanation on why and the way how 5G is being replaced by 6G.
Keywords: Wireless networks; 5G technology; networks; 6G Technology